2010
DOI: 10.1007/s00125-010-1691-2
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol efflux via ATP-binding cassette transporter A1 (ABCA1) and cholesterol uptake via the LDL receptor influences cholesterol-induced impairment of beta cell function in mice

Abstract: Aims/hypothesis Cellular cholesterol accumulation is an emerging mechanism for beta cell dysfunction in type 2 diabetes. Absence of the cholesterol transporter ATP-binding cassette transporter A1 (ABCA1) results in increased islet cholesterol and impaired insulin secretion, indicating that impaired cholesterol efflux leads to beta cell dysfunction. In this study, we aimed to determine the role of the LDL receptor (LDLr) in islet cholesterol uptake and to assess the contributions of cholesterol uptake compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
95
3
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(107 citation statements)
references
References 30 publications
7
95
3
2
Order By: Relevance
“…via LDL receptor) is also an important source of this sterol for islets (Kruit et al 2010). However, it is not only the cholesterol sources, but also their interplay in the mechanisms responsible for its efflux determines cholesterol homeostasis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…via LDL receptor) is also an important source of this sterol for islets (Kruit et al 2010). However, it is not only the cholesterol sources, but also their interplay in the mechanisms responsible for its efflux determines cholesterol homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is not only the cholesterol sources, but also their interplay in the mechanisms responsible for its efflux determines cholesterol homeostasis. The cholesterol transporter ABCA1 appears to be a key regulator of cholesterol efflux, because ABCA1 K/K mouse islets presented high cholesterol content with a consequent disruption of GSIS (Kruit et al 2010(Kruit et al , 2011. This negative effect on b-cell function due to accumulation of cholesterol has also been shown in the overactivation of its sources.…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that these patients did not present the characteristic markers of the metabolic syndrome (including visceral obesity, hypertriglyceridemia, hypertension, and insulin resistance) nor a positive family history of diabetes. The pathophysiology of the Tangier disease model has been confirmed in ABCA1 knock-out animals, which exhibited both an increased development of cardiovascular lesions and a progressive impairment of glucose tolerance [45]. The preserved insulin sensitivity demonstrated in these animals suggests that the impaired glucose regulation is exclusively linked to a direct toxic effect of cholesterol on the beta-cell [44].…”
Section: Dyslipidemia Contributing To Diabetes and Vascular Complicatmentioning
confidence: 91%
“…To this end, various researchers have clearly described specific receptors for LDL-C, namely LRPs, present in pancreatic islets, and they showed that LDL-C particles are incorporated in the metabolic pathway of beta-cells in a highly selective manner [44,45]. However, this increased bioavailability of LDL-C in the pancreatic cell metabolism seems to have a cytotoxic effect, and may cause increased beta-cell apoptosis.…”
Section: Dyslipidemia Contributing To Diabetes and Vascular Complicatmentioning
confidence: 99%
“…To the Editor: In a recent issue of Diabetologia, Kruit and colleagues presented an article regarding the role of cholesterol-induced impairment of beta cell function in mice [1]. The authors found that in Ldlr -/-knockout mice, which lack the LDL receptor, islet cholesterol content was normal despite moderate hypercholesterolaemia, and in the presence of very high plasma cholesterol levels induced by a Western-style diet, glucose-stimulated insulin secretion was not reduced.…”
Section: Abca1 Atp-binding Cassette Transporter A1mentioning
confidence: 99%